Effect of Distal Interlocking Screw Number and Position After Intramedullary Nailing of Distal Tibial Fractures: A Biomechanical Study Simulating Immediate Weight-Bearing. Issue 2 (February 2015) - Chan, Daniel S.; Nayak, Aniruddh N.; Blaisdell, Greg; James, Chris R.; Denard, Antony; Miles, Jeremy; Santoni, Brandon G.
Abstract : Objective: To quantify the changes in biomechanical stability conferred by the addition of a single medial blocking screw or a single bicortical interlocking screw to 2 existing distal points of screw fixation in a distal tibial fracture model repaired with intramedullary nailing. Methods: After simulation of a distal tibial metaphyseal fracture, 21 synthetic tibiae were repaired with an intramedullary nail and: (1) two bicortical locking screws placed in the 2 most distal screw holes (IM-L2); (2) three distal bicortical locking screws (IM-L3); and 2 distal locking screws and a single blocking screw positioned in the sagittal plane on the medial aspect of the nail (IM-L2B). The specimens were tested under combined cyclic axial and torsional loading for up to 16k cycles. The former was stepwise increasing, whereas the latter was with constant amplitude in internal rotation. Results: All constructs survived 12k cycles without hardware deformation or failure. IM-L3 constructs displayed the highest baseline axial stiffness at the beginning of the test (1130.9 ± 246.9 N/mm), which was significant compared with the IM-L2 construct (701.8 ± 189.57 N/mm, P = 0.004). No significant difference in baseline axial stiffness was identified between the IM-L3 and IM-L2B constructs (881.1 ± 182.4 N/mm, P = 0.125). Relative varus interfragmentary deformation at baseline was smaller in the IM-L3 treatment group (1.3 ± 0.3 degrees) relative to the IM-L2 group (2.4 ± 0.7 degrees, P = 0.012). No differences in torsional rigidity or relative interfragmentary torsional deformation were identified between groups ( P > 0.168). Failure was breakage or backout of the distal bicortical screws, fracture of the distal fragment, or proximal screw breakage. There was no significant difference in number of cycles to failure between instrumentation groups (IM-L2: 14, 345 ± 1438 cycles; IM-L3: 15, 634 ± 626 cycles; and IM-L2B: 14, 862 ± 1511 cycles, P = 0.184). Conclusion: Results suggest that each of the constructs tested here may be a biomechanically viable option allowing for immediate weight-bearing after fixation of fractures of the distal third of the tibia. The addition of a single bicortical interlocking screw to create 3 points of distal fixation improves construct stiffness while reducing interfragmentary motion relative to 2 interlocking points of screw fixation with or without a blocking screw.